Аналіз застосування генетичних алгоритмів в задачах глобальної оптимізації - Мороз, О.Г. (Управляющие системы и машины, 2018)
Подано загальну характеристику генетичних алгоритмiв як ефективних та перспективних засобiв вирiшення проблеми глобальної оптимiзацiї. Розглянуто приклади складних реальних задач оптимiзацiї та iдентифiкацiї, успiшно розв’язаних iз застосуванням генетичних алгоритмiв. Цель. Подробно рассмотреть теоретические и практические аспекты ГА и их возможности для решения задач оптимизации и идентификации систем.
Методы. Цель статьи достигается путем представления всестороннего обзора основных публикаций в области теории генетических алгоритмов и их применения для эффективного решения сложных задач оптимизации.
Результаты. Рассмотрены теоретические и прикладные аспекты ГА. Приведены примеры современных глобальных задач оптимизации и идентификации моделей, успешно решаемых генетическими алгоритмами. Purpose. The purpose of the research is to examine more comprehensively the theoretical and practical aspects of the genetic algorithms and their capabilities for solving optimization and system identification problems.
Methods. The goal of this article is achieved by presenting a comprehensive survey of the main publications in the area of genetic algorithms theory and their application to the complex optimization tasks.
Results. The theoretical and applied aspects of genetic algorithms are considered in detail. Some examples of modern global optimization and model identification problems successfully solved by genetic algorithms are presented.